2013
DOI: 10.1007/s13105-013-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced changes of MCT1 in cardiac and skeletal muscles of diabetic rats induced by high-fat diet and STZ

Abstract: We hypothesized that a part of therapeutic effects of endurance training on insulin resistance is mediated by increase in cardiac and skeletal muscle mitochondrial lactate transporter, monocarboxylate transporter 1 (MCT1). Therefore, we examined the effect of 7 weeks endurance training on the mRNA and protein expression of MCT1 and MCT4 and their chaperon, CD147, on both sarcolemmal and mitochondrial membrane, separately, in healthy and type 2 diabetic rats. Diabetes was induced by injection of low dose of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Only this high dose of STZ induced weight loss, and produced a plasma metabolite profile that included hyperketonaemia, hyperlipidaemia, and hypoinsulinaemia. This is in agreement with other studies that have used high doses of STZ in isolation or in combination with high-fat feeding [19,36-39], with these high doses also causing abnormalities in liver morphology and function [25]. In contrast, the lower doses of STZ investigated in the present study avoided these extreme phenotypes, instead presenting with hyperglycaemia in the absence of ketosis, normoinsulinaemia and with maintenance of body weight.…”
Section: Discussionsupporting
confidence: 93%
“…Only this high dose of STZ induced weight loss, and produced a plasma metabolite profile that included hyperketonaemia, hyperlipidaemia, and hypoinsulinaemia. This is in agreement with other studies that have used high doses of STZ in isolation or in combination with high-fat feeding [19,36-39], with these high doses also causing abnormalities in liver morphology and function [25]. In contrast, the lower doses of STZ investigated in the present study avoided these extreme phenotypes, instead presenting with hyperglycaemia in the absence of ketosis, normoinsulinaemia and with maintenance of body weight.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that MCT4 expression and its location on plasma membrane were decreased under HG and IL-1b condition in HUVECs. Nikooie et al demonstrated that diabetes dramatically reduced MCT4 mRNA and their expression on sarcolemmal membrane [26]. Thus, the decrease of MCT4 may be involved in inflammation and metabolic changes (hyperglycemia).…”
Section: Discussionmentioning
confidence: 99%
“…2000 ng of total RNA was added to each 40 μl cDNA synthesis reaction, which was reverse transcribed to cDNA using iScript Reverse Transcription Supermix (BioRad). Primer sequences, annealing temperatures and product sizes for quantitative real-time PCR are shown in Table 1 (14,15). Primers were validated by running endpoint PCR with 250 nM forward and reverse primers, 1 μl of cDNA and iTaq Universal SYBR Green Supermix (BioRad) following the manufacturer's instructions.…”
Section: Animals Estrus Staging and Tissue Collectionmentioning
confidence: 99%